1990
DOI: 10.1002/hlca.19900730513
|View full text |Cite
|
Sign up to set email alerts
|

Rh(II)‐Catalyzed Isomerizations of Cyclopropenes Evidence for Rh(II)‐Complexed Vinylcarbene Intermediates

Abstract: The thermocatalytic rearrangements of cyclopropenes 1 4 have been investigated in the presence of Rh(I1) perfluorobutyrate. 1,2,3-Triphenylcyclopropene (la) undergoes rearrangement to diphenylindene 5a or, with alkoxycyclopropene derivatives, to ccJ-unsaturated ketone 6. Furan formation occurs with 2,3-diphenylcyclopropenecarboxylate 2, but the diethyl counterpart 3 rearranges to dienoate 8.2-Alkylcyclopropenecarboxylates 4 afforded (E)-methylidenecyclopentane derivatives9 as the only isolable product in yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…In all cases studied so far, the less-substituted cyclopropene single bond was smore [12b] (see Introduction), metalϪcarbene complexes 7 do not rearrange to vinylcarbene complexes 12 and 13 cleaved, but the final product pattern was found to be sensitive to the catalyst. Both the copper- [34,36] and the rhodium-(which also implies that 7 and 13 are not connected by metallacyclobutene 8) With regard to the electrophilic nature catalyzed [36] isomerization of cyclopropene-3-carboxylates (a substructure also present in 9) to form 2-alkoxyfurans of 7 (cf. resonance structure 7Ј), cationic attack at the acetylenic bond would give rise to vinyl cations 14 and 15. have been reported.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In all cases studied so far, the less-substituted cyclopropene single bond was smore [12b] (see Introduction), metalϪcarbene complexes 7 do not rearrange to vinylcarbene complexes 12 and 13 cleaved, but the final product pattern was found to be sensitive to the catalyst. Both the copper- [34,36] and the rhodium-(which also implies that 7 and 13 are not connected by metallacyclobutene 8) With regard to the electrophilic nature catalyzed [36] isomerization of cyclopropene-3-carboxylates (a substructure also present in 9) to form 2-alkoxyfurans of 7 (cf. resonance structure 7Ј), cationic attack at the acetylenic bond would give rise to vinyl cations 14 and 15. have been reported.…”
Section: Resultsmentioning
confidence: 98%
“…In fact, inspection of a molecular model suggests that 11 does not only have a higher ring strain due to the prerepresent the precursor of oxasilines 3, and 13 would account for the formation of products 2, 4, and 6. Copper-sence of a carbenium center at the ring fusion but also adopts a conformation in which the endo-R 3 substituent at [33Ϫ36] and rhodium-catalyzed [20,36,37] ring-opening reactions of cyclopropenes are amply documented. Interest-silicon is situated over the concave face of the bicyclic framework.…”
Section: Resultsmentioning
confidence: 99%
“…The groups of Müller and Doyle [17,18,19], Padwa [20], and Gevorgyan [21] also documented formation of furans as side products in the cyclopropenation reactions of alkynes catalyzed by Rh(II) carboxylate complexes. Evidence for the carbenoid nature of the cyclopropene to furan rearrangement was also obtained by Müller and Doyle, who found that cycloisomerization of cyclopropenylcarboxylate 34 catalyzed by Rh 2 pfb 4 produced cyclopentylidene acetate 36 as a major product along with traces of furan 38 (Scheme 9) [17][18][19].…”
Section: Methodsmentioning
confidence: 98%
“…In view of the known preference of Rh" complexed carbenes for CH insertions [32], the thermocatalytic rearrangements of 15 and 21 in the presence of [Rh,(PFB),] (PFB = perfluorobutyrate) were also investigated, but without success. Reaction of 15 (60°, benzene, 6 % of catalyst) gave exclusively 1,2,3-triphenylprop-2-enone, which probably results from triphenylcyclopropenium ion, while 21 was recovered unchanged after exposure to 4% of [Rh,(PFB),] (OO, toluene).…”
Section: Pxmentioning
confidence: 99%